The submicron particles FORMULATION OF IONIC-GELATION SUBMICRON PARTICLES LOADING EXTRACT PAPAYA LEAVES (Carica papaya L.) WITH LACTIC ACID ISOLATES - Mardiyanto, Mardiyanto; Untari, Budi; Fithri, Najma Annuria; Sandi, Sofia; Mawaddah, Zahrul (Science and Technology Indonesia, 2019)
A study regarding ionic-gelation submicron particle of papaya leaves (Carica papaya L.) extract with lactic acid of weeds potentially for antidiarrhea has been conducted. Preparation of papaya leaves ethanolic extract and lactic acid isolate into particles was done by ionic gelation method. This study aimed to determine: the major compound of extract, the total quercertine of extract, the percent value of encapsulation efficiency of the optimum formula which was varied by (CaOH)2 of the three formulas, and physical properties of particles. Formula 1 was using (CaOH)2 of 12.5 gram; formula 2 (CaOH)2 of 17,5 gram; formula 3 (CaOH)2 of 22.5 gram. The results showed formula 1 as the optimum formula that has the highest %EE. The average %EE values ??of F1; F2; F3 respectively were 80,82%; 80,41%; 80,31%. The results of particle characterization using the PSA in the optimum formula produced particle size values ??with an average of 253.6 nm, PDI of 0.218, and zeta potential +8 mV respectively.